The art of life and death : radical aesthetics and ethnographic practice - Irving, Andrew (Chicago, IL : Hau Books, 2017)
The Art of Life and Death explores how the world appears to people who have an acute perspective on it: those who are close to death. Based on extensive ethnographic research, Andrew Irving brings to life the lived experiences, imaginative lifeworlds, and existential concerns of persons confronting their own mortality and non-being. Encompassing twenty years of working alongside persons living with HIV/AIDS in New York, Irving documents the radical but often unspoken and unvoiced transformations in perception, knowledge, and understanding that people experience in the face of death. By bringing an “experience-near” ethnographic focus to the streams of inner dialogue, imagination, and aesthetic expression that are central to the experience of illness and everyday life, this monograph offers a theoretical, ethnographic, and methodological contribution to the anthropology of time, finitude, and the human condition. With relevance well-beyond the disciplinary boundaries of anthropology, this book ultimately highlights the challenge of capturing the inner experience of human suffering and hope that affect us all—of the trauma of the threat of death and the surprise of continued life. --
Beginnings : the limits of the world -- Thrown out of the world : a city of flesh and stone -- Detours and puzzles in the land of the living : toward an imperiled anthropology -- To live that life -- Rethinking anthropology from a pragmatic point of view -- A disintegration of the senses -- The eternal return -- You only live twice.
Keywords: elämä; kuolema; kuolevaisuus (filosofia); kokemukset; livet; döden; dödlighet (filosofi); erfarenheter